2020
DOI: 10.17126/joralres.2019.061
|View full text |Cite
|
Sign up to set email alerts
|

The most common oral lesions in edentulous patients with total prostheses.

Abstract: A group of 210 patients with total maxillary and mandibular prostheses were examined to identify the main pathological alterations suffered by edentulous patients. The observed results determined that the average age at which the largest edentulous population is found is between 56 and 65 years with a higher prevalence of females. Of these more than 50% have used oral prostheses for more than 12 years with an adequate hygiene quality in 116 patients where the most frequent oral pathology associated with edentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…In contrast to other studies [ 9 , 12 , 13 ], the authors found no significant relationship with gender. However, age was an important risk factor.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other studies [ 9 , 12 , 13 ], the authors found no significant relationship with gender. However, age was an important risk factor.…”
Section: Discussioncontrasting
confidence: 99%
“…Edentulous patients are also more likely to suffer from oral mucosal lesions related to the wearing of removable prosthesis [9][10][11][12][13][14]. The most commonly seen denture-related oral mucosal lesions (DOML) are stomatitis, hyperplasia, angular cheilitis and traumatic ulcers [9][10][11][12][13][14]. DOML was also seen more frequently in patients who wore complete dentures as opposed to removable partial dentures [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation